2020
DOI: 10.33889/ijmems.2020.5.4.058
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Few Nature Inspired Optimization Techniques and Its Reliability Applications

Abstract: Optimization has been a hot topic due to its inevitably in the development of new algorithms in almost every applied branch of Mathematics. Despite the broadness of optimization techniques in research fields, there is always an open scope of further refinement. We present here an overview of nature-inspired optimization with a subtle background of fundamentals and classification and their reliability applications. An attempt has been made to exhibit the contrast nature of multi objective optimization as compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Future work can also extend the number of echelons in a supply chain beyond the two-echelon problem as was the case in this study. Apart from that, novel and computationally efficient metaheuristics proposed in the literature, such as Grey Wolf Optimization (Negi et al, 2021), Flower Pollination Algorithm (Pant et al, 2017a), Cuckoos Search Algorithm, have demonstrated promising results in other research areas (Kumar et al, 2019;Pant et al, 2017b;Uniyal et al, 2020). This study can be extended by exploring one of these metaheuristics to obtain better results.…”
Section: Conclusion and Future Researchmentioning
confidence: 86%
“…Future work can also extend the number of echelons in a supply chain beyond the two-echelon problem as was the case in this study. Apart from that, novel and computationally efficient metaheuristics proposed in the literature, such as Grey Wolf Optimization (Negi et al, 2021), Flower Pollination Algorithm (Pant et al, 2017a), Cuckoos Search Algorithm, have demonstrated promising results in other research areas (Kumar et al, 2019;Pant et al, 2017b;Uniyal et al, 2020). This study can be extended by exploring one of these metaheuristics to obtain better results.…”
Section: Conclusion and Future Researchmentioning
confidence: 86%
“…The multi-criterion decision-making (MCDM) tool of grey-analytical hierarchy process (G-AHP) has been implemented in the study to prioritize the drivers of SHCSC performance measurement. The MCDM technique considers the uncertainty and vagueness of thoughts at the time of decision-making (Mirjalili et al, 2014;Thakur and Ramesh, 2017;Pant et al, 2017aPant et al, , b, 2019Kumar et al, 2019;Uniyal et al, 2020;Negi et al, 2021). The G-AHP methodology is the combination of the advantage of the grey system theory and the classical analytic hierarchy process (AHP).…”
Section: Literature On the Solution Methodologymentioning
confidence: 99%
“…They focused on increasing the operational time of the individual components of a system to maintain higher system reliability and improve productivity and profit by the application of nature-inspired optimization techniques such as Grey Wolf Optimization (GWO) and the Cuckoo Search Algorithm (CSA). Uniyal et al (2020) reviewed nature-inspired optimization along with a background of fundamentals, classification, and their reliability applications. They also demonstrate the difference between multi-objective optimization and singleobjective optimization.…”
Section: Metaheuristics In Solving Jsspmentioning
confidence: 99%